Structure‐Property Relations of Nickel and Cobalt Substituted Yttrium Aluminum Garnets as Catalyst Materials for Dry Reforming of Methane. Issue 11 (7th September 2022) - Fritsch, Charlotte; Titus, Juliane; Roussière, Thomas; Lizandara‐Pueyo, Carlos; Müller, Robert; Gläser, Roger; Schunk, Stephan Andreas
Abstract: Nickel‐ and cobalt‐substituted yttrium aluminum garnets (YAGs) were synthesized varying their stoichiometries and the details of the thermal treatment procedures at elevated temperatures. Ni and/or Co substitution into the framework of Y3 Al5 O12 was found to be feasible up to molar metal contents of 6 mol %. The synthesis conditions were optimized towards a compromise of high phase purity of the high‐temperature phase of YAG, still maintaining sensible specific surface areas of the resulting catalyst materials. The two synthetic procedures evaluated in the study allow introduction of nickel and cobalt into the oxidic framework of the YAG oxide, from which under reducing conditions, both metals can be exsolved. The catalysts were studied in the catalytic dry reforming of methane under stoichiometric ratio of CO2 /CH4 at atmospheric pressure. The catalytic results indicate that for the best candidate materials performance is stable and a syngas of the desired ratio n H2 / n CO = 1 is formed. Trends were observed towards nickel being the catalytically more active metal compared to cobalt. Abstract : High‐purity Ni‐ and Co‐ substituted YAGs were tested under CO2 /CH4 atmosphere for dry reforming of methane for 15 h. Trends were observed towards Ni being the catalytically more active metal compared to Co, which suffers from higher amounts of carbon deposition, probably formed by methane cracking.